Vocational Teachers and Vocational Teacher Training Model - Nguyen , Xuân Mai (Journal of Technical Education Science, 2008)
The development of human resource is being the top priority of the Party and the State. The strategic objective to be achieved is to increase the number of trained labourers by 40% by 2010. To this end, the teachers play a vital role. Resolutions No. 37 of National Assembly has clearly stated: “It is essential to have suitable structure of teachers with adequate quality and quantity in all industries”. However, with current training models, training quality can not be assured. In terms of quantity of teachers, the ratio of teachers/students is only equivalent to half of the required standard ratio. As such, if the training scale is to be double by 2010, the number of vocational teachers will be considerably deficient. In terms of structure, the vocational system is currently providing training for 186 different vocational areas. Meanwhile, our technical pedagogic schools are able to train teachers in only 21 areas. There is no school training teachers for the remaining 165 vocational areas. Therefore, training vocational schools are experiencing a tough period in the face of the demands for developing vocational training of the coming time. Research on, and seeking for, new solutions, new models for improving quality, increasing quantity, expanding scale and areas of training for vocational teachers no meet the demand for rapid development of vocational system in the coming time are very hot issue nowadays.